2011
DOI: 10.1158/1538-7445.am2011-5201
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5201: Distinctive distribution of expression of Lgr5, an intestinal stem cell marker, during each stage of colorectal tumorigenesis

Abstract: Lgr5, an orphan G-protein coupled receptor and Wnt target gene, has been identified as a murine intestinal stem cell marker. To elucidate the role of Lgr5 during each stage of human colorectal tumorigenesis, we immunohistochemically analyzed 17 low-grade, 13 high-grade intraepithelial neoplasias and 30 adenocarcinomas. While there was only sporadic expression of Lgr5 at the crypt base in normal epithelia, the increased numbers of Lgr5-positive cells were found in most tumors, with clustering of the cells to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 0 publications
10
57
2
1
Order By: Relevance
“…4d), mimicking the LGR5 expression pattern in healthy colon tissue. In contrast, LS174T cells that expressed GalNAc-T6 had a high number of LGR5-positive cells in the upper layers of the colonies, with increasing staining intensity at the luminal surface, similar to the expression pattern of LGR5 in human colon cancer (73). This may indicate that GalNAc-T6 expression induces a cancer-like LGR5 expression pattern in these colonies (Fig.…”
Section: Cancer-associated Expression Of Human Pp-galnac-t6mentioning
confidence: 71%
“…4d), mimicking the LGR5 expression pattern in healthy colon tissue. In contrast, LS174T cells that expressed GalNAc-T6 had a high number of LGR5-positive cells in the upper layers of the colonies, with increasing staining intensity at the luminal surface, similar to the expression pattern of LGR5 in human colon cancer (73). This may indicate that GalNAc-T6 expression induces a cancer-like LGR5 expression pattern in these colonies (Fig.…”
Section: Cancer-associated Expression Of Human Pp-galnac-t6mentioning
confidence: 71%
“…Many studies have found that LGR5 expression is higher in tumor tissues than in adjacent nontumor tissues and promotes cell proliferation and tumor formation [21,37,38]. However, another study suggested that LGR5 was a negative regulator of tumorigenicity in colorectal carcinomas [39].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal CSCs (CCSC) have been distinguished using CD44 or CD133 either alone (8)(9)(10), or combined with other markers, such as EpCAM, CD166, CD29, CD24, LGR5 and aldehyde dehydrogenase 1 (ALDH1; refs. [11][12][13]. Previous studies by ourselves and other authors have shown that as few as 100 CD44 þ cancer cells isolated from patients were able to develop into a heterogeneous tumor, and that spheroids derived from a single CD44 þ cancer cell could recapitulate the heterogeneous hierarchy of tumor cells (8,14).…”
Section: Introductionmentioning
confidence: 92%